2019
DOI: 10.1115/1.4042583
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Die Casting With Uncertainty Quantification

Abstract: Die casting is a type of metal casting in which a liquid metal is solidified in a reusable die. In such a complex process, measuring and controlling the process parameters are difficult. Conventional deterministic simulations are insufficient to completely estimate the effect of stochastic variation in the process parameters on product quality. In this research, a framework to simulate the effect of stochastic variation together with verification, validation, and uncertainty quantification (UQ) is proposed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The single objective response surfaces were used to get an insight regarding the conflicting nature of the objectives since the individual optimal solutions were completely different from each other. Moreover, the solidification time, maximum grain size and minimum yield strength varied in the ranges [2, 3.5] seconds, [22,34] microns and [134, 145] MPa respectively for the given inputs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The single objective response surfaces were used to get an insight regarding the conflicting nature of the objectives since the individual optimal solutions were completely different from each other. Moreover, the solidification time, maximum grain size and minimum yield strength varied in the ranges [2, 3.5] seconds, [22,34] microns and [134, 145] MPa respectively for the given inputs.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, we have first generated a tetrahedral mesh using GMSH [20] and then divided into a hexahedral mesh using TETHEX [21]. The details of the numerical algorithm and verification and validation of OpenCast are discussed in previous publications [15,22]. A model geometry representing a clamp [15] has been considered to illustrate the methodology.…”
Section: Numerical Model Descriptionmentioning
confidence: 99%
“…In this experimental work, the specimen component was extracted from pressure die casting for analyzing various properties. 35,36…”
Section: Experimental Work and Proceduresmentioning
confidence: 99%
“…Several successful studies have been also reported in using physics informed deep learning models [14][15][16] to directly solve the partial differential equations (PDEs), governing some of these the physical laws and processes. Neural networks have also been used as surrogate models coupled with computational methods for sensitivity analysis [17], uncertainty quantification [18][19][20][21][22], inverse problems [23] and design optimization [24,25].…”
Section: Introductionmentioning
confidence: 99%